Bất định chính sách kinh tế Việt Nam và đầu tư doanh nghiệp - Dương Thị Thùy, An (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
In the context of increasing global and domestic policy and macroeconomic uncertainty, this study examines the impact of economic policy uncertainty on firms’ capital expenditure (fixed asset investment) decisions. This paper employs the Vietnam-specific economic policy uncertainty indices developed by Hoang et al. (2025), which disaggregate uncertainty into monetary, fiscal, and trade components. Using financial data from 1,373 Vietnamese firms during 2016–2023 and a multi-way fixed effects model, this paper finds that economic policy uncertainty negatively affects capital expenditures, with fiscal and monetary policy uncertainty exerting the strongest effects. Importantly, this negative relationship persists even among high-performing firms, suggesting that uncertainty weakens investment incentives regardless of operational efficiency. Ownership structure plays a moderating role: Privately owned enterprises are more sensitive to economic policy uncertainty than their state-owned counterparts, while foreign-owned enterprises exhibit no significant response. These findings offer important policy implications for policymakers, investors, and firms in coping with macroeconomic risks.
Keywords: Fixed capital formation; Trade policy uncertainty; Fiscal policy uncertainty; Monetary policy uncertainty; Economic policy uncertainty